2019
DOI: 10.1177/2319714519863559
|View full text |Cite
|
Sign up to set email alerts
|

Learning from Quality Audit in Higher Education Institutions: A Tool for Community Engagement Enhancement

Abstract: Higher education institutions (HEIs) are asked more and more to be community engaged. In fact, governments have become more sensitive regarding the role and the contributions of these institutions in the development of the society in general and students’ skills in specific. Community engagement (CE) has also become an important part of the quality accreditation framework in several countries. Through this, researchers tried to demonstrate a positive correlation between the publication of the quality audit rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…However, the Higher Education Institutions are no longer perceived as the sole and unique entity responsible of the capacities [77]. Joint and coordinated action is required from all educational agents, from both the public and private sectors, and from society in general.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Higher Education Institutions are no longer perceived as the sole and unique entity responsible of the capacities [77]. Joint and coordinated action is required from all educational agents, from both the public and private sectors, and from society in general.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement requires affirmation, recognition, and recommendation taken from each high education level's report for helping an institutional audit team describe its high education level (Kooli, Jamrah, & Al-Abri, 2019).…”
Section: Art and Creativitymentioning
confidence: 99%
“…Riehl (2000) explored the roles of administrators when reacting to various students' needs. Three tasks of principal as a school administrator that need to be underlined are: developing the new meaning of diversity, promoting inclusivity related to school's culture and its teaching programs, and promoting the relation among school and community that in fact, the research of Kooli et al (2019) has shown that in Oman, there are many high education levels hold programs without awareness of students' needs and abilities while an audit panel has not focused on evaluating high education levels' performances. Riehl offered a positive perspective about the potential of principals to be included in the practice of inclusive and transformative education.…”
Section: Leadership Stylesmentioning
confidence: 99%
“…Through their creative talents and labour power, a nation makes giant strides in economic development [11]. In their dreams and hopes a nation founds her motivation; on their energies, she builds her vitality and purpose through effective and constructive use of production ventures like employment creation, engagement in economic production, academic and community development activities, [12] sports, setting good moral standard among others. Moreover, as a result of their dreams and aspirations, the assurance of the future is made and secured.…”
Section: Conceptual Insightsmentioning
confidence: 99%